Osteogenic Response to Polysaccharide Nanogel Sheets of Human Fibroblasts After Conversion Into Functional Osteoblasts by Direct Phenotypic Cell Reprogramming - Nakai, Kei; Yamamoto, Kenta; Kishida, Tsunao; Kotani, Shin-ichiro; Sato, Yoshiki; Horiguchi, Satoshi; Yamanobe, Hironaka; Adachi, Tetsuya; Boschetto, Francesco; Marin, Elia; Zhu, Wenliang; Akiyoshi, Kazunari; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Human dermal fibroblasts (HDFs) were converted into osteoblasts using a ALK inhibitor II (inhibitor of transforming growth factor-β signal) on freeze-dried nanogel-crosslinked porous (FD-NanoClip) poly-saccharide sheets or fibers. The ability was then analyzed of these directly converted osteoblasts (dOBs) to produce calcified substrates and the expression of osteoblast genes in comparison with osteoblasts converted by exactly the same procedure but seeded onto a conventional atelocollagen scaffold. dOBs exposed to FD-NanoClip both in sheet and fiber morphologies produced a significantly higher concentration of calcium deposits as compared to a control cell sample (i.e., unconverted fibroblasts), while there was no statistically significant difference in calcification level between dOBs exposed to atelocollagen sheets and the control group. The observed differences in osteogenic behaviors were interpreted according to Raman spectroscopic analyses comparing different polysaccharide scaffolds and Fourier transform infrared spectroscopy analyses of dOB cultures. This study substantiates a possible new path to repair large bone defects through a simplified transplantation procedure using FD-NanoClip sheets with better osteogenic outputs as compared to the existing atelocollagen scaffolding material.